Effectiveness and safety of traditional Chinese medical bath therapy combined with ultraviolet irradiation in the treatment of psoriasis: A systematic review and meta-analysis of randomized controlled trials. - Jingzhi Guan; Shaofei Yuan; Hanqimuge Wu; Risu Na; Xueqin Wu; Xin Wang; Shan Bao (PLoS ONE)
Background and objective To systematically evaluate the clinical effects and safety of traditional Chinese medical bath therapy (TCMBT) combined with ultraviolet irradiation in the treatment of psoriasis. Methods Electronic database retrieval was utilized. The foreign retrieval databases consulted included those of the Cochrane Library, PubMed and EMBASE; the domestic retrieval databases included the Chinese Biomedical Literature Database (Sino-Med), the China National Knowledge Infrastructure (CNKI), VIP and the WangFang Database. Clinical randomized controlled trials were conducted to evaluate the effects of TCMBT combined with ultraviolet irradiation in the treatment of psoriasis; the language of the retrieved articles was Chinese or English. Each database was searched from its inception to August 1, 2015. Two researchers independently collected the data and analyzed the methodology of the documented literature. The researchers conducted a meta-analysis with RevMan 5.2.3 software. Results According to the available literature, 25 RCTs (randomized controlled trials) of low research quality were conducted. According to the meta-analysis, the total effective rate of TCMBT combined with ultraviolet irradiation was relatively higher than that of ultraviolet irradiation alone. The recurrence rate, incidence of adverse reactions and Psoriasis Area and Severity Index (PASI) for the combined therapy was lower than that of ultraviolet irradiation (P<0.05). Conclusion For the treatment of psoriasis, the clinical effects and safety of TCMBT combined with ultraviolet irradiation are generally better than those of ultraviolet irradiation alone. However, the original literature was written in Chinese, and the quality of the studies was not high. Thus, it is difficult to confirm the clinical effects and safety of TCMBT combined with ultraviolet irradiation. It is necessary to conduct a scientific, normalized and high-quality RCT with multiple large samples and centers.